Tourist cluster and theoretical and methodological aspects of its management and evaluation of investment attractiveness - A. V. Saprykina (Путеводитель предпринимателя)
The tourism industry in Russia is not currently a priority sector, forming a significant part of the national GDP. But, according to most experts and scientists, the Russian tourism industry has a great and unused potential, which can be mastered using a cluster approach (through the creation of tourist clusters). Within the framework of the presented article, the main theoretical concepts defining the essence of tourist clusters in the economy are presented, as well as the basic methods for studying the investment attractiveness of both the clusters themselves and the tourism and hospitality spheres in general.